Differential intervention needs according to the r-n-r model: Evidence from an empirical typology of Brazilian adolescent offenders - Sette Galinari, Lais (2025)
The theoretical and methodological model of Risk-Need-Responsiveness considers intervention needs to be those dynamic aspects that should be worked on in an intervention context with a focus on preventing recidivism. The aim of the study was to characterize interventional needs of different profiles. The sample consisted of 4 profiles, composed by 400 adolescents in conflict with the law and ANOVA and Bonferroni post-test analyses were carried out. It was found that the four profiles differed in terms of the interventional needs identified as relevant to be assessed according to the R-N-R model. The results reinforce the hypothesis of heterogeneity among adolescents in conflict with the law, which would require differential and personalized interventions.